Clinical outcome, recanalization success, and time metrics in drip-and-ship vs. drive-the-doctor: A retrospective analysis of the HEI-LU-Stroke registry - Urbanek, Christian; Jung, Jasmin; Güney, Resul; Potreck, Arne; Nagel, Simon; Grau, Armin J.; Boujan, Timan; Luckscheiter, Andre; Bendszus, Martin; Möhlenbruch, Markus A.; Seker, Fatih (Frontiers in Neurology, 2023)
PURPOSE: This study aimed at comparing clinical outcome, recanalization success and time metrics in the “drip and ship” (DS) versus “drive the doctor” (DD) concept in a comparable setting. METHODS: This is a retrospective analysis of thrombectomy registries of a comprehensive stroke center (CSC) and a thrombectomy-capable stroke center (TSC). Patients, who were transferred from the TSC to the CSC, were classified as DS. Patients treated at the TSC by an interventionalist transferred from the CSC were classified as DD. Good outcome was defined as mRS 0-2 or equivalent to premorbid mRS at discharge. Recanalization (TICI 2b-3 or equivalent) and time metrics were compared in both groups. RESULTS: In total, 295 patients were included, of which 116 (39.3%) were treated in the DS concept and 179 (60.7%) in the DD concept. Good clinical outcome was similarly achieved in DS and DD (DS 25.0% vs. DD 31.3%, P=0.293). mRS on discharge (DS median 4, DD median 4, P=0.686), NIHSS improvement (DS median 4, DD median 5, P=0.582) and NIHSS on discharge (DS median 9, DD median 7, P=0.231) were similar in both groups. Successful reperfusion was achieved similarly in DS (75.9%) and DD as well (81.0%, P=0.375). Time from onset to reperfusion (median DS 379 vs. DD 286 min, P=0.076) and time from initial imaging to reperfusion were longer in DS compared to DD (median DS 246 vs. DD 162 min, P<0.001). CONCLUSION: The DD concept is time saving while achieving similar clinical outcome and recanalization results.